A regionalization method for theater modeling - Lukić Darko; Blagojević Srđan; Stojadinović Ivan; Sekulović Dragoljub (Glasnik Srpskog Geografskog Društva, 2025)
The paper researches the principles and methods of geographic regionalization that, with the application of spatial analysis and GIS techniques, can support the modeling of geographic space for military operations. The concept of solving the problem of logically defined and interconnected steps of regionalization of the geographic space of the Republic of Serbia was applied. The research problem was performed based on the principle of region zoning based on the homogeneity of the geographic space using the GIS Spatial Overlay Method. Regionalization was implemented on the principle of fundamental region zoning and using the GIS Spatial Overlay Method. The goal of applying the model is to create a new military-territorial organization of the geographic space of the Republic of Serbia through overlapping thematic layers, formed according to the principle of homogeneity of the geographical space. Theater or specific military fundamental regions were obtained. In the paper, the authors implemented a statistical procedure for assessing the homogeneity and dispersion of geographical factors based on the coefficient of variation (CV). In this way, the degree of homogeneity of the obtained region was determined, which contributed to the evaluation of the objectivity of the applied model. The model conceived in this way showed the possibility of successful application in the regionalization of geographical space for military purposes. The model is suitable for the regionalization of a similar or different geographical space where the key principle is the homogeneity of geographical factors.